Algorithms and data structures : an approach in C - Bowman, Charles F. (Oxford University Press, 1994)
With numerous practical, real-world algorithms presented in the C programming language, Bowman's Algorithms and Data Structures: An Approach in C is the algorithms text for courses that take a modern approach. For the one- or two-semester undergraduate course in data structures, it instructs students on the science of developing and analyzing algorithms. Bowman focuses on both the theoretical and practical aspects of algorithm development. He discusses problem-solving techniques and introduces the concepts of data abstraction and algorithm efficiency. More importantly, the text does not present algorithms in a "shopping-list" format. Rather it provides actual insight into the design process itself
Keywords: C (Computer program language); Computer algorithms.; Data structures (Computer science); Algorithms.; elektronické knihy; electronic books